2023
DOI: 10.7759/cureus.34650
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Assessment With European Organisation for Research and Treatment of Cancer Questionnaire (Head and Neck Module 43) and Its Clinicopathological Correlation Among Patients Treated for Oral Squamous Cell Carcinoma: An Exploratory Study

Abstract: IntroductionOral cancer has a great impact on quality of life (QOL). Many risk factors influence the overall QOL. Our study was performed to evaluate the QOL among patients with oral cancer and to correlate it with age, gender, tobacco usage, and clinicopathological details. MethodsWe have used the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Head and Neck Module (EORTC QLQ-HN43) and the Quality of Life Questionnaires for Core 30 (QLQ-C30) among the patients diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…To enhance the patient's health-related quality of life, the surgeon should therefore strive for a minimal resection followed by the best repair required for the patient's age and illness stage. Sufficient counseling must be provided [ 16 ]. This study states that the QOL of the patient should be considered before we decide on the treatment plan, and in this audit, we came to know that they are maintaining regular follow-ups for the patient, and counseling for the patient is also provided.…”
Section: Discussionmentioning
confidence: 99%
“…To enhance the patient's health-related quality of life, the surgeon should therefore strive for a minimal resection followed by the best repair required for the patient's age and illness stage. Sufficient counseling must be provided [ 16 ]. This study states that the QOL of the patient should be considered before we decide on the treatment plan, and in this audit, we came to know that they are maintaining regular follow-ups for the patient, and counseling for the patient is also provided.…”
Section: Discussionmentioning
confidence: 99%
“…However, when activating receptors are stimulated, NK cells exert cytotoxic effects and exhibit high levels of anti-tumor activity. Studies have shown that in cancers, the levels of activating receptors (NCR1, NCR2, NCR3) are decreased, and this finding has been linked to poor prognosis [ 14 ]. However, their role in oral premalignant lesions needs to be better elucidated in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Quality of life assessment is very critical for patients with OSCC [ 14 ]. Early diagnosis has a crucial role in determining the long-term prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…They also exhibit anxiety about surviving a cancer diagnosis and receiving future treatment [2,3]. The European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Head and Neck Module (EORTC QLQ-HN43) is a revised and updated version of the Head and Neck Cancer Module (QLQ-HN35) [4,5]. It is a supplementary questionnaire module with the General Quality of Life Questionnaire Core 30 (QLQ-C30).…”
Section: Background and Introductionmentioning
confidence: 99%